Research Progress of Clinical Treatment for Narrow and Calcified Root Canals - Yuxiang TANG; Weidong YANG (国际转化医学杂志（英文版）, 2019)
The aim of root canal treatment was to clean the resident microbiota through proper shaping, disinfection and obturation of the root canal system in order to achieve periapical healing, Calcification of the pulp chamber and root lumen can compromise access and thus complicate the root canal therapy. The process of calcific metamorphosis, also known as root canal obliteration was very common in elder people or young permanent teeth with trauma. With the help of dental operating microscope (DOM), ultrasonic techniques, C-Pilot files, ethylenediaminetetraacetic acid (EDTA), and other novel instruments, it became possible to locate the canal orifices and negotiate the root cavity in severe calcified root canal systems, leaving the dentist with a promising technical prospect of clinical skills. Accordingly, it is necessary to get known to different clinical techniques, choose selectively in different cases, that may led to good results, even in difficult situation.